2018
DOI: 10.1007/jhep02(2018)137
|View full text |Cite
|
Sign up to set email alerts
|

The massless integer superspin multiplets revisited

Abstract: We propose a new off-shell formulation for the massless N = 1 supersymmetric multiplet of integer superspin s in four dimensions, where s = 2, 3, . . . (the s = 1 case corresponds to the gravitino multiplet). Its gauge freedom matches that of the superconformal superspin-s multiplet described in arXiv:1701.00682. The gaugeinvariant action involves two compensating multiplets in addition to the superconformal superspin-s multiplet. Upon imposing a partial gauge fixing, this action reduces to the one describing … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 32 publications
(67 reference statements)
1
33
0
Order By: Relevance
“…In [39] it was demonstrated that for the matter gravitino supermultiplet [Y = 1] (3/2, 1) one can relax the Poincaré gauge transformation to match the conformal one, by adding another compensating superfield with an algebraic (no derivatives) transformation law. Recently [20] this mechanism was applied to higher integer superspin supermultiplets. However, this description is non-economical (requires more superfields than it is necessary) and one can always use the algebraic nature of the transformation of the additional compensator in order to remove it.…”
Section: Anti-linear Transformation Of the Chiral Superfieldmentioning
confidence: 99%
“…In [39] it was demonstrated that for the matter gravitino supermultiplet [Y = 1] (3/2, 1) one can relax the Poincaré gauge transformation to match the conformal one, by adding another compensating superfield with an algebraic (no derivatives) transformation law. Recently [20] this mechanism was applied to higher integer superspin supermultiplets. However, this description is non-economical (requires more superfields than it is necessary) and one can always use the algebraic nature of the transformation of the additional compensator in order to remove it.…”
Section: Anti-linear Transformation Of the Chiral Superfieldmentioning
confidence: 99%
“…Massless models given in this section will serve as the building blocks for our construction of the massive was considered in [12]. The superfield approach was recently applied for construction of the higher spin supercurrents [13], [14], [15]. [16], [17], [18], [19].…”
Section: Introductionmentioning
confidence: 99%
“…• General non-conformal deformations of the conformal supercurrents J α(n)α(n) and J α(n+1)α(n) , eq. (4.15), were described in [64,100,101] for the cases of Minkowski and AdS backgrounds. Various aspects of such non-conformal higher-spin supercurrents in Minkowski superspace were studied in [102][103][104].…”
Section: Resultsmentioning
confidence: 99%